OPTIMISING BEAUTY BRAND COMMUNITY MANAGEMENT THROUGH A LARAVEL-BASED WEB SYSTEM - Hanna Mariana Angelika; Bhustomy Hakim (Jurnal Teknoinfo, 2025)
Globalisation has accelerated advancements in technology, communication, and information systems, intensifying competition across industries. In response, companies are adopting marketing communication strategies to build stronger relationships with consumers. One such strategy involves establishing brand communities, particularly within the beauty industry. In Indonesia, several beauty brands have established brand communities to enhance customer interaction and strengthen brand loyalty. One such brand, referred to here as DRS, specifically targets individuals aged 17 to 30. These communities typically offer initiatives such as point rewards, educational webinars, interactive challenges, product sampling, and early access to new products. However, DRS continues to manage its community manually through messaging platforms and basic data records. This manual approach results in several operational inefficiencies, including disorganised communication, data entry errors, and delays in programme validation, all of which undermine administrative performance and reduce overall member satisfaction and engagement. To address these issues, this study proposes a web-based brand community management system with two main components. The first is a management interface used by administrators and superadministrators. The second is a user platform accessed by account users and members. Key features include programme management, discussion forums, point redemption, leaderboards, and reporting functionalities. The system also incorporates principles from learning management systems to support continuous interaction, progress tracking, and sustained member engagement. It is developed using the Waterfall model of the software development life cycle, which supports structured planning and documentation. Laravel is selected as the development framework because of its efficiency, scalability, and model-view-controller architecture. The system is tested using the Black Box Testing method, and the results show that all functionalities operate according to the defined specifications. This system is expected to improve operational efficiency, enhance member experience and engagement, strengthen brand loyalty, enhance brand awareness and brand image, and support sustainable growth for beauty brands in Indonesia, particularly for brand DRS.